2018
DOI: 10.2196/jmir.9670
|View full text |Cite
|
Sign up to set email alerts
|

Pokémon GO and Physical Activity in Asia: Multilevel Study

Abstract: BackgroundPhysical activity has long been considered as an important component of a healthy lifestyle. Although many efforts have been made to promote physical activity, there is no effective global intervention for physical activity promotion. Some researchers have suggested that Pokémon GO, a location-based augmented reality game, was associated with a short-term increase in players’ physical activity on a global scale, but the details are far from clear.ObjectiveThe objective of our study was to study the r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
2
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 45 publications
1
69
2
4
Order By: Relevance
“…this would possibly indicate that PG did not have an additional impact on physical activity in those who were already active. it would be consistent with the conclusion of another study that playing PG was most beneficial to players who were inactive prior to the investigation [28,29].…”
Section: Discussionsupporting
confidence: 90%
“…this would possibly indicate that PG did not have an additional impact on physical activity in those who were already active. it would be consistent with the conclusion of another study that playing PG was most beneficial to players who were inactive prior to the investigation [28,29].…”
Section: Discussionsupporting
confidence: 90%
“…More recently, an augmented reality exergame run on smartphones, Pokémon Go, has seen over 800 million downloads [19]. A study conducted in Hong Kong (participants N=210; aged 16 to 64 years) found that the use of Pokémon Go was associated with a short-term increase in the players’ daily walking and running distances, particularly in those who were less physically active [20].…”
Section: Introductionmentioning
confidence: 99%
“…As with humans, plants and their microbiomes form a holobiont, and the interplay between the plant host and its co-evolving microbial assemblages has a substantial role in maintaining the health of these functional ecological units [94]. Microbial diversity is a key driving factor in maintaining favorable plant health [94,95].…”
Section: Microbiome-inspired Green Infrastructure-plant Microbiome Sementioning
confidence: 99%
“…As with humans, plants and their microbiomes form a holobiont, and the interplay between the plant host and its co-evolving microbial assemblages has a substantial role in maintaining the health of these functional ecological units [94]. Microbial diversity is a key driving factor in maintaining favorable plant health [94,95]. Indeed, individual plant genotypes can show distinct microbial diversity, which indicates that some plants have the ability to cultivate a beneficial microbiome and this process may be under natural selection [96].…”
Section: Microbiome-inspired Green Infrastructure-plant Microbiome Sementioning
confidence: 99%